A retrospective study to assess and correlate maternal periodontal status with term of pregnancy and weight of newborn - Jain, Mayuri N.; Suragimath, Girish; Varma, Siddhartha A.; Zope, Sameer Anil; S. R., Ashwini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Periodontitis is an inflammatory disease affecting the tooth supporting structures; studies have shown that it also affects the systemic health and conditions like pregnancy. With this background the present retrospective study was conducted to assess and correlate periodontal status of pregnant women with their pregnancy outcome. Methods: A total of 150 pregnant women two days postpartum were examined for periodontal status using following parameters: Oral hygiene index- simplified (OHI-S), modified gingival index (MGI), probing pocket depth (PPD) and clinical attachment loss (CAL). The level of education, body mass index (BMI), gestational age and weight of the baby were recorded and correlated with the periodontal status. Results: Out of 150 women, 83 (55.3%) women suffered from gingivitis and 67 (44.7%) had periodontitis. The incidence of preterm low birth weight babies was seen in 65 (43.33%) women. Body mass index, education level and periodontal disease were significantly associated with preterm low birth weight infants. Conclusions: A significant association was found between periodontitis and preterm low birth infants. The promotion of early detection and treatment of periodontal diseases in women before and during pregnancy will be beneficial. This will minimize the cost of post natal care and morbidity in the new born.